2013
DOI: 10.1051/0004-6361/201220747
|View full text |Cite
|
Sign up to set email alerts
|

The identification of 93 day periodic photometric variability for YSO YLW 16A

Abstract: Aims. Periodic variability in young stellar objects (YSOs) offers indirect evidence for an active dynamical mechanism. Starspots, accretion, stellar companions, and disk veiling can contribute to the photometric variability of YSOs. Methods. As part of an ongoing study of the ρ Oph star forming region, we report the discovery of 92.6 day periodic variations for the Class I YSO YLW 16A, observed over a period of three years. A SED model was fit to available photometric data for the object. Results. We propose a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…Wider binaries can experience periodic dimming as components of the binary pass behind a circumbinary disk, as is the case in KH 15D (e.g., Windemuth & Herbst 2014;Arulanantham et al 2016). The 131-day-period WL 4 system and the 93-day-period YLW 16A system (Plavchan et al 2013) show similar dimming behavior, suggesting a similar origin for their variability. A companion misaligned with the disk can also drag material out of the midplane (Fragner & Nelson 2010), leading to periodic occultations of the primary star.…”
Section: Discussionmentioning
confidence: 85%
“…Wider binaries can experience periodic dimming as components of the binary pass behind a circumbinary disk, as is the case in KH 15D (e.g., Windemuth & Herbst 2014;Arulanantham et al 2016). The 131-day-period WL 4 system and the 93-day-period YLW 16A system (Plavchan et al 2013) show similar dimming behavior, suggesting a similar origin for their variability. A companion misaligned with the disk can also drag material out of the midplane (Fragner & Nelson 2010), leading to periodic occultations of the primary star.…”
Section: Discussionmentioning
confidence: 85%
“…Companions are also invoked in several examples of presumed disk-eclipsing young stars that, like PTF 10nvg, have long periods. Specifically, KH15D at 48 days (Hamilton et al 2012), WL4 at 131 days (Plavchan et al 2008), and YLW16A at 92 days (Plavchan et al 2010) have extinction-like flux dips between a few tenths and several magnitudes in depth. Several of these stars have companions in the 25-50 AU region that are hypothesized to induce warps in the disks.…”
Section: Constraints On Multiplicitymentioning
confidence: 98%
“…Other well-known low-amplitude young star variables such as UX Ori, RR Tau, VV Ser, AA Tau as well as the "dippers" discussed by Morales-Calderón et al (2011) and Cody & Hillenbrand (2010, 2011) also appear to be undergoing short timescale extinction events. Larger amplitude and-importantly-longperiod examples include KH15D (Hamilton et al 2012), WL4 (Plavchan et al 2008), and YLW16A (Plavchan et al 2010), which have found explanation in binary interactions with circumstellar disk material.…”
Section: Introductionmentioning
confidence: 99%
“…Although thousands of PMS stars have been photometrically monitored in the past years, only few objects show a variable behaviour that resembles KH 15D, i.e. YLW 16A and WL 4 in ρ Oph (Plavchan et al 2010(Plavchan et al , 2008, and V718 Per in IC 348 (Grinin et al 2008). In the case of WL 4 and YLW 16A, the authors proposed the existence of a new class of periodic disc-eclipsing binaries to explain the KH 15D type variability, in which a third body in these systems is responsible for the warping of the inner circumbinary disc needed to produce the eclipses, while Grinin et al (2008) argued that V718 Per is most probably a single star surrounded by an edge-on circumstellar disc with an irregular mass distribution at the inner edge of the disc, which causes the observed periodic variability.…”
Section: Introductionmentioning
confidence: 99%